Retention of afforestation areas as part of flood protection - research site and methodology for headwater watershad in Poland = Retencja leśna zlewni jako element ochrony przeciwpowodziowej - Orczykowski, Tomasz; Tiukało, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Land use is considered as a non-structural, ecologically beneficial flood protection measure. Forest as one of the land use types has many useful applications which can be observed in detail on www.nwrm.eu website project. It is scientifically proved that afforestation influences flood events with high probability of occurrence. However, it is still to be argued how to measure land use impact on the hydrological response of watershed and how it should be measured in an efficient and quantifiable way.
Keywords: naturalna retencja; modelowanie hydrologiczne; użytkowanie terenu; ochrona przeciwpowodziowa; natural water retention measures; hydrological modelling; land use; flood protection